Predictive value of neutrophil-lymphocyte ratio and platelet-lymphocyte ratio in patients with vaginitis: nested case-control study - Ali Mohammed Ali Al-Nuaimi (Folia Medica)
Aim: To investigate the value of the hematological indices to differentiate bacterial vaginosis (BV) from vulvovaginal candidiasis (VVC) and predict treatment response. Materials and methods: This nested case-control study included 390 women divided into three groups: healthy women, women diagnosed with BV, and women diagnosed with VVC. Additionally, two groups (BV and VVC) were treated and followed prospectively until cured. Demographic data, blood indices, and high-sensitivity C-reactive protein (hsCRP) were obtained from the women. Results: hsCRP and neutrophil-lymphocyte ratio (NLR) showed the best diagnostic utility to predict BV with AUC=0.721 and 0.735, respectively. hsCRP showed the best specificity (99.23%), while NLR showed the best sensitivity (82.31%) to differentiate BV. Regarding percentage change after treatment, NLR showed a higher reduction percentage in the BV group (−27.41±8.151%) than VVC (0.158±5.804%). Conclusions: NLR is an efficient diagnostic instrument for distinguishing individuals with bacterial vaginosis from those with vulvovaginal candidiasis. Its diagnostic reliability is comparable to more regularly used markers such as WBC and hsCRP. Both NLR and PLR are good predictors of clinical response to treatment in bacterial vaginosis.